Polarizing film laminate

CN116482791BActive Publication Date: 2026-10-09NITTO DENKO CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310062412.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-11-15
Filing Date
2023-01-19
Publication Date
2026-10-09
Estimated Expiration
2043-01-19

AI Technical Summary

Technical Problem

[0003]然而,在上述这种空间内设置有个人电脑、电视机、显示器等图像显示装置的情况下,可以从外部观察到其显示内容,因此在信息安全、个人隐私方面是不优选的

Benefits of technology

[0023] According to embodiments of the present invention, by providing a support to the polarizing film laminate and setting the adhesive force of the second adhesive layer to a specific range, it is possible to easily peel off after being adhered to an object, and it can also be re-adheded and reprocessed. Furthermore, it is possible to prevent peeling or detachment over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116482791B_ABST
    Figure CN116482791B_ABST
Patent Text Reader

Abstract

To provide a polarizing film laminate which is reworkable and has excellent long-term adhesion. The polarizing film laminate of the embodiment has a structure in which a polarizing plate including a polarizing member, a first adhesive layer, a support substrate, and a second adhesive layer are sequentially stacked, and the glass adhesion (peeling angle 90°, peeling speed 300 mm / min) of the second adhesive layer is 1.0 N / 25 mm or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polarizing film laminate and a partition wall on which the polarizing film laminate is adhered. Background Technology

[0002] In recent years, in order to achieve bright and open work and living spaces, designs have been made to increase the ratio of windows on walls and doors that separate spaces, and to turn entire walls and doors into windows.

[0003] However, if a personal computer, television, monitor, or other image display device is installed in such a space, the displayed content can be observed from the outside, which is not preferable in terms of information security and personal privacy.

[0004] In response, the following technology has been proposed: by attaching a polarizing plate with an adhesive layer to a window in such a way that its absorption axis direction is parallel to the vibration direction of the linearly polarized light emitted from the display screen of the aforementioned image display device, the displayed content can no longer be observed from the outside (e.g., Non-Patent Document 1).

[0005] Existing technical documents

[0006] Non-patent literature

[0007] [Non-Patent Literature 1] KUROGANE KOSAKUSHO LTD., Comprehensive Product Catalog [2020 Edition, Vol. 45, p. 110] Summary of the Invention

[0008] The problem the invention aims to solve

[0009] However, the adhesives used in conventional polarizing plates with adhesive layers are designed for use in image display devices and are difficult to peel off once applied, resulting in insufficient reprocessability. To address this issue, the inventors attempted to improve reprocessability by increasing the peelability of the adhesive layer (by lightly peeling off the adhesive layer), but found that this resulted in peeling and flaking over time.

[0010] The present invention was made to solve the above-mentioned problems, and its main objective is to provide a polarizing film laminate that is reprocessable and has excellent long-term adhesion.

[0011] Solution for solving the problem

[0012] According to one aspect of the present invention, a polarizing film laminate is provided, having a structure in which a polarizing plate including a polarizing element, a first adhesive layer, a supporting substrate and a second adhesive layer are sequentially stacked, wherein the second adhesive layer has a glass adhesion force (peel angle 90°, peel speed 300 mm / min) of 1.0 N / 25 mm or more.

[0013] In one embodiment, the water absorption rate of the aforementioned support substrate is less than 5.0%.

[0014] In one embodiment, water is applied to the surface of the second adhesive layer and / or the surface of the glass plate that is the object to be bonded. While pressing the glass plate with water squeezed out from their interface between the second adhesive layer and the glass plate, the adhesion force to the glass (peel angle 90°, peel speed 300 mm / min) after 4 days from the time of pressing is 0.2 N / 25 mm to 5.0 N / 25 mm.

[0015] In one embodiment, the polarizing plate further includes a protective layer disposed on at least one side of the polarizing element.

[0016] In one embodiment, the support substrate includes a substrate body and a functional layer disposed on at least one side of the substrate body.

[0017] In one embodiment, the functional layer is at least one layer selected from the antistatic layer and the antifouling layer.

[0018] In one embodiment, the thickness from the polarizing plate to the second adhesive layer is 50 μm to 500 μm.

[0019] In one embodiment, a release liner is laminated on the side of the second adhesive layer opposite to the side on which the support substrate is configured.

[0020] According to another aspect of the present invention, a partition wall is provided, which is a transparent partition wall that separates the space of an image display device having linearly polarized light emitted from the display screen inside. The polarizing film laminate is bonded by means of the second adhesive layer, such that the absorption axis of the polarizing element is substantially parallel to the vibration direction of the linearly polarized light emitted by the image display device.

[0021] In one embodiment, the aforementioned partition wall is a window, wall, door, or partition.

[0022] The effects of the invention

[0023] According to embodiments of the present invention, by providing a support to the polarizing film laminate and setting the adhesive force of the second adhesive layer to a specific range, it is possible to easily peel off after being adhered to an object, and it can also be re-adheded and reprocessed. Furthermore, it is possible to prevent peeling or detachment over time. Attached Figure Description

[0024] Figure 1A This is a cross-sectional schematic diagram of a polarizing thin film laminate according to one embodiment of the present invention.

[0025] Figure 1B This is a cross-sectional schematic diagram of a polarizing thin film laminate according to another embodiment of the present invention.

[0026] Figure 2A This is a cross-sectional schematic diagram of an example of a support substrate that can be used in this invention.

[0027] Figure 2B This is a cross-sectional schematic diagram of an example of a support substrate that can be used in this invention.

[0028] Figure 2C This is a cross-sectional schematic diagram of an example of a support substrate that can be used in this invention.

[0029] Figure 3 This is a schematic diagram illustrating an example of a partition wall of a polarizing thin film laminate according to an embodiment of the present invention.

[0030] Explanation of reference numerals in the attached figures

[0031] 10 polarizing plates

[0032] 12 polarizers

[0033] 14 Inner protective layer

[0034] 16 outer protective layers

[0035] 20 First adhesive layer

[0036] 30 Supporting Substrate

[0037] 32 Substrate Body

[0038] 34 Functional Layers

[0039] 40 Second adhesive layer

[0040] 50 Peeling Pad

[0041] 60 Protective Substrate

[0042] 100 polarizing thin film laminate

[0043] 200 walls

[0044] 210 walls

[0045] 220 walls

[0046] 230 walls

[0047] 240 ceiling

[0048] 250 floor

[0049] 300 space

[0050] 400 Image Display Device Detailed Implementation

[0051] The preferred embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.

[0052] A. Polarizing film laminate

[0053] The polarizing film laminate of the present invention has a structure in which a polarizing plate including a polarizing element, a first adhesive layer, a supporting substrate and a second adhesive layer are stacked in sequence.

[0054] A-1. Overall structure of the polarizing thin film laminate

[0055] Figure 1A This is a cross-sectional schematic diagram of a polarizing film laminate according to one embodiment of the present invention. The polarizing film laminate 100a has a structure in which a polarizing plate 10a, a first adhesive layer 20, a support substrate 30, and a second adhesive layer 40 are sequentially laminated, and can be adhered to transparent components such as window glass by means of the second adhesive layer 40. Furthermore, in the polarizing film laminate 100a, a release liner 50 is laminated (temporarily bonded) on the surface of the second adhesive layer 40 opposite to the side where the support substrate 30 is disposed. The release liner 50 is temporarily bonded until it is used in the polarizing film laminate 100a, protecting the second adhesive layer 40. Although not shown, a surface protective film can be temporarily bonded to the surface of the polarizing plate 10a opposite to the side where the first adhesive layer 20 is disposed until it is used in the polarizing film laminate 100a.

[0056] Figure 1B This is a cross-sectional schematic diagram of a polarizing film laminate according to another embodiment of the present invention. The polarizing film laminate 100b has a structure in which a protective substrate 60, a polarizing plate 10b, a first adhesive layer 20, a supporting substrate 30, and a second adhesive layer 40 are sequentially laminated, and can be adhered to transparent components such as window glass by means of the second adhesive layer 40. Furthermore, a release liner 50 is laminated (temporarily bonded) on the surface of the second adhesive layer 40 opposite to the side where the supporting substrate 30 is provided. By providing the protective substrate 60 on the outer side of the polarizing plate (the side opposite to the side where the first adhesive layer is provided), the polarizing film laminate can be endowed with scratch resistance, splash resistance, non-flammability, etc. The protective substrate 60 is attached to the polarizing plate 10b by means of any suitable adhesive layer (adhesive layer or adhesive layer). Although not shown, a surface protective film can be temporarily bonded to the surface of the protective substrate 60 opposite to the side where the polarizing plate 10b is provided until it is used in the polarizing film laminate 100b.

[0057] The total thickness (t1) from the polarizing plate of the polarizing film laminate to the second adhesive layer is preferably 50 μm to 500 μm, more preferably 100 μm to 250 μm. This thickness provides good workability for bonding, peeling, etc. Furthermore, when the polarizing film laminate has a protective substrate, the total thickness (t2) from the protective substrate of the polarizing film laminate to the second adhesive layer is preferably 50 μm to 2.5 mm, more preferably 100 μm to 2.0 mm. This thickness allows for the production of polarizing film laminates with scratch resistance, splash resistance, and non-flammability without compromising workability.

[0058] The adhesion strength of the second adhesive layer of the polarizing film laminate to glass is typically 1.0 N / 25 mm or more, preferably 2.0 N / 25 mm or more, and more preferably 2.5 N / 25 mm or more. The adhesion strength of the second adhesive layer of the polarizing film laminate to glass can, for example, be 10 N / 25 mm or less, 9.0 N / 25 mm or less, or 6.0 N / 25 mm or less. If the adhesion strength to glass is within the above range, both reprocessability and long-term adhesion can be achieved. It should be noted that, in this specification, the glass adhesion strength is measured at a peel angle of 90° and a peel speed of 300 mm / min. Furthermore, in this specification, unless otherwise specified, the glass adhesion strength is a value measured according to JIS Z0237, and is measured 30 minutes after the test sample is directly pasted (dry application) onto the substrate without water.

[0059] The monomer transmittance of the polarizing film laminate (in the state after the release liner has been removed) is preferably 30% or more, more preferably 35% to 45%, and practically preferably 35% to 43%. If the monomer transmittance is in this range, a more open space can be achieved.

[0060] The following is a more detailed explanation of the constituent elements of the polarizing thin film laminate.

[0061] A-2.Polarizing plate

[0062] A polarizing plate includes a polarizing element. The polarizing plate may further include, as needed, a protective layer disposed on one or both sides of the polarizing element. For example, Figure 1A The polarizing plate 10a shown includes a polarizing element 12, an inner protective layer 14 disposed on the side of the first adhesive layer 20 of the polarizing element 12, and an outer protective layer 16 disposed on the side of the polarizing element 12 opposite to the side where the first adhesive layer 20 is disposed. On the other hand, Figure 1BThe polarizing plate 10b shown includes a polarizing element 12 and an outer protective layer 16 disposed on the side of the polarizing element 12 opposite to the side where the first adhesive layer 20 is disposed, having a structure that omits the inner protective layer. Although not shown, the polarizing plate may also include a polarizing element and an inner protective layer, with the outer protective layer omitted.

[0063] A-2-1. Polarizing element

[0064] The polarizer 12 is typically made of a polyvinyl alcohol resin film containing a dichroic substance (such as iodine). The polarizer can be made of a single layer of resin film or can be made of a laminate of two or more layers.

[0065] Specific examples of polarizers composed of single-layer resin films include: films obtained by dyeing and stretching hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films using dichroic substances such as iodine and dichroic dyes; and polyene-oriented films such as dehydrated PVA products and dehydrochlorinated polyvinyl chloride products. Polarizers obtained by dyeing PVA films with iodine and then uniaxially stretching them are preferred due to their excellent optical properties.

[0066] The aforementioned dyeing using iodine is performed, for example, by immersing a PVA film in an aqueous iodine solution. The preferred stretching ratio for the uniaxial stretching is 3 to 7 times. Stretching can be performed after dyeing or during dyeing. Dyeing can also be performed after stretching. The PVA film can be subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc., as needed. For example, by immersing the PVA film in water for washing before dyeing, not only can dirt and anti-blocking agents on the surface of the PVA film be removed, but also swelling of the PVA film and uneven dyeing can be prevented.

[0067] Specific examples of polarizing elements obtained using laminates include: polarizing elements obtained using a resin substrate and a PVA-type resin layer (PVA-type resin film) laminated on the resin substrate, or a resin substrate and a PVA-type resin layer coated on the resin substrate. A polarizing element obtained using a resin substrate and a PVA-type resin layer coated on the resin substrate can be manufactured, for example, by the following steps: coating a PVA-type resin solution onto a resin substrate, drying it, forming a PVA-type resin layer on the resin substrate, obtaining a laminate of the resin substrate and the PVA-type resin layer; stretching and dyeing the laminate to form a polarizing element from the PVA-type resin layer. In this embodiment, stretching typically includes: immersing the laminate in an aqueous boric acid solution for stretching. Furthermore, stretching may, as needed, further include: air stretching the laminate at a high temperature (e.g., above 95°C) before stretching in the aqueous boric acid solution. The resulting resin substrate / polarizer laminate can be used directly (i.e., the resin substrate can be used as a protective layer for the polarizer), or the resin substrate can be peeled off from the resin substrate / polarizer laminate and any suitable protective layer for the purpose can be laminated on the peeled surface. Details of this method for manufacturing polarizers are described, for example, in Japanese Patent Application Publication No. 2012-73580. The entire contents of that publication are incorporated herein by reference.

[0068] The thickness of the polarizing element is, for example, 30 μm or less, preferably 15 μm or less, more preferably 1 μm to 12 μm, even more preferably 2 μm to 10 μm, and particularly preferably 2 μm to 8 μm. By reducing the thickness of the polarizing element, dimensional changes during or after application to the substrate can be suppressed, thus improving workability and preventing peeling.

[0069] The polarizer preferably exhibits absorption dichroism at any wavelength from 380 nm to 780 nm. The transmittance of the polarizer is preferably 38.6% to 46.0%, more preferably 40.0% to 43.0% or 43.0% to 46.0%. The polarization degree of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0070] A-2-2. Protective Layer

[0071] The inner protective layer 14 and the outer protective layer 16 can be formed from any suitable thin film, as long as they can function as protective layers for the polarizing element. Specific examples of materials constituting the main components of the thin film include: cellulose resins such as cellulose triacetate (TAC); transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrene, polynorbornene, polyolefins, (meth)acrylic acids, and acetates. Furthermore, thermosetting or UV-curing resins such as (meth)acrylic acids, urethanes, (meth)acrylate urethanes, epoxy resins, and silicone resins can also be used. In addition, glassy polymers such as siloxane polymers can also be used. Furthermore, polymer films described in Japanese Patent Application Publication No. 2001-343529 (WO01 / 37007) can also be used. As a material for the film, for example, a resin composition containing a thermoplastic resin having substituted or unsubstituted imide groups in the side chains, and a thermoplastic resin having substituted or unsubstituted phenyl and nitrile groups in the side chains can be used. Examples include resin compositions having alternating copolymers formed from isobutylene and N-methylmaleimide, and acrylonitrile-styrene copolymers. The polymer film can be, for example, an extruded product of the above-mentioned resin compositions.

[0072] At least one of the inner and outer protective layers is preferably optically isotropic. Specifically, when the polarizing film laminate is bonded to the outer surface (outer side of the space) of a partition wall that separates the space in which the image display device is disposed, the inner protective layer is preferably optically isotropic. Furthermore, when the polarizing film laminate is bonded to the inner surface (inner side of the space) of the partition wall that separates the space in which the image display device is disposed, the outer protective layer is preferably optically isotropic. It should be noted that, in this specification, "optically isotropic" means that the in-plane phase difference Re(550) is 0 nm to 10 nm, and the phase difference Rth(550) in the thickness direction is -10 nm to +10 nm. "Re(550)" is the in-plane phase difference measured at 23°C using light with a wavelength of 550 nm, calculated using the formula: Re = (nx - ny) × d. Furthermore, "Rth(550)" is the phase difference in the thickness direction measured at 23°C using light with a wavelength of 550 nm, calculated using the formula: Rth=(nx-nz)×d. Here, "nx" is the refractive index in the direction where the refractive index reaches its maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction orthogonal to the slow axis (i.e., the fast axis direction), "nz" is the refractive index in the thickness direction, and "d" is the thickness (nm) of the layer (thin film).

[0073] A hard coating can be applied to the outer surface of the outer protective layer (i.e., the side opposite to the polarizer side) as needed. Specific examples of materials constituting the hard coating include: thermosetting resins, thermoplastic resins, active energy radiation-cured resins (e.g., UV-cured resins, electron beam-cured resins), and two-component blended resins. UV-cured resins are preferred because the hard coating can be formed efficiently with simple processing operations.

[0074] The thickness of the hard coating is preferably 1 μm to 20 μm, more preferably 2 μm to 15 μm.

[0075] The thicknesses of the inner and outer protective layers (the total thickness including the thickness of the hard coating when a hard coating is provided) are preferably 10 μm to 250 μm, more preferably 20 μm to 150 μm, even more preferably 25 μm to 100 μm, and even more preferably 25 μm to 50 μm.

[0076] A-3. Supporting substrate

[0077] The support substrate 30 includes a substrate body made of a resin film. The support substrate may consist only of the substrate body, or, if needed, may further include functional layers on one or both sides of the substrate body. For example... Figures 2A to 2C These are cross-sectional schematic diagrams of an example of a support substrate that can be used in this invention. Figure 2A The support substrate 30a shown includes a substrate body 32 and a functional layer 34 disposed on the first adhesive layer side of the substrate body 32. Figure 2B The support substrate 30b shown includes a substrate body 32 and a functional layer 34 disposed on the second adhesive layer side of the substrate body 32. Figure 2C The support substrate 30c shown includes a substrate body 32 and functional layers 34a and 34b sequentially disposed on the first adhesive layer side of the substrate body 32.

[0078] The support substrate effectively supports the polarizing plate when the polarizing film laminate is adhered to the substrate and when it is temporarily peeled off from the substrate for reprocessing. Furthermore, the polarizing plate can expand or contract due to ambient temperature and / or humidity, causing dimensional changes. Therefore, when the polarizing plate is adhered to the substrate using only the first adhesive layer without the second adhesive layer and support substrate, the first adhesive layer alone cannot fully absorb the dimensional changes of the polarizing plate, sometimes resulting in curling, lifting, or peeling of the polarizing film laminate. In contrast, by providing the second adhesive layer and support substrate, such curling or lifting / peeling can be suppressed. Moreover, since polarizing plates are prone to cracking, careful peeling is required during reprocessing. Even with careful peeling, cracking sometimes occurs. Therefore, by providing the support substrate with the first adhesive layer and adhering it to the substrate using the second adhesive layer, cracking can be prevented and peeling can be performed easily. This effect of the support substrate is particularly advantageous when using polarizing plates without an inner protective layer.

[0079] The water absorption rate of the support substrate is preferably 5.0% or less, more preferably 4.5% or less, and even more preferably 4.0% or less (e.g., 1.5% or less or 1.0% or less). The aforementioned effects can be suitably obtained if the water absorption rate is within this range. It should be noted that the water absorption rate can be determined according to ASTM D570 (24h-3.18mm thickness).

[0080] A-3-1. Substrate Body

[0081] As the substrate, any suitable resin film can be used, as long as it can support the polarizing plate. Examples of resin films constituting the substrate include: polyester resin films, cycloolefin resin films, acrylic resin films, cellulose ester resin films, cellulose resin films, polyester carbonate resin films, olefin resin films, polyurethane resin films, polycarbonate resin films, and polyvinyl acetal resin films. Polyester resin films, acrylic resin films, or polycarbonate resin films are preferred. These resins can be used alone or in combination according to desired properties.

[0082] Examples of polyester resins included in polyester resin films include polyethylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, and polyethylene terephthalate. Polyethylene terephthalate and polyethylene naphthalate are preferred examples of polyester resins, and polyethylene terephthalate is more preferred.

[0083] Examples of acrylic resins included in acrylic resin films include: poly(meth)acrylates such as polymethyl methacrylate, methyl methacrylate-(meth)acrylate copolymers, methyl methacrylate-(meth)acrylate copolymers, methyl methacrylate-acrylate-(meth)acrylate copolymers, methyl methacrylate-styrene copolymers (MS resin, etc.), and polymers having alicyclic hydrocarbon groups (e.g., methyl methacrylate-cyclohexyl methacrylate copolymers, methyl methacrylate-norborneol ester copolymers, etc.). Acrylic resins can have anhydride groups such as glutaric anhydride and succinic anhydride as structural units. For example, by using maleic anhydride as a copolymerizing component, acrylic polymers with a succinic anhydride structure can be obtained. It should be noted that in this specification, "(meth)acrylate" refers to acrylic acid and / or methacrylic acid. Acrylic resins include resins with acrylic acid or its derivatives as constituent monomers, and resins with methacrylic acid or its derivatives as constituent monomers.

[0084] As the polycarbonate resin contained in a polycarbonate film, aromatic polycarbonate is preferred. Aromatic polycarbonates are typically obtained by reacting a carbonate precursor with an aromatic divalent phenolic compound. Specific examples of carbonate precursors include phosgene, dichloroformates of divalent phenols, diphenyl carbonate, di-p-tolyl carbonate, phenyl-p-tolyl carbonate, di-p-chlorophenyl carbonate, and dinaphthyl carbonate. Among these, phosgene and diphenyl carbonate are preferred. Specific examples of aromatic divalent phenolic compounds include: 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)butane, 2,2-bis(4-hydroxy-3,5-dipropylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane. These can be used alone or in combination of two or more. 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane are preferred. It is particularly preferred to use 2,2-bis(4-hydroxyphenyl)propane and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane together.

[0085] The thickness of the substrate is preferably 5μm to 250μm, more preferably 10μm to 150μm, and even more preferably 20μm to 100μm.

[0086] The substrate can be treated with surface treatments such as corona treatment, or coated with silane coupling agents, as needed.

[0087] A-3-2. Functional Layer

[0088] Examples of functional layers include antistatic layers, anti-fouling layers, printable layers, and easy-to-adhere layers. A single functional layer can be used, or a combination of two or more functional layers can be employed. For example... Figure 2A The functional layer 34 shown is preferably an antistatic layer, an anti-fouling layer, or a printing layer, and more preferably an antistatic layer. Furthermore, for example... Figure 2B The functional layer 34 shown is preferably an antistatic layer. Furthermore, for example... Figure 2C The functional layer 34a shown is preferably an antistatic layer or a printed layer, and the functional layer 34b is preferably an antifouling layer.

[0089] The antistatic layer typically comprises a conductive material and an adhesive resin. Any suitable conductive material can be used as the conductive material. Conductive polymers are preferred. Examples of conductive polymers include: polythiophene polymers, polyacetylene polymers, polydiacetylene polymers, polyacetylene polymers, polyphenylene polymers, polynaphthalene polymers, polyfluorene polymers, polyanthracene polymers, polypyrene polymers, polychaete polymers, polypyrrole polymers, polyfuran polymers, polyselenophene polymers, polyisothiaindelineated polymers, polyoxadiazole polymers, polyaniline polymers, polythiazole polymers, polyphenylacetylene polymers, polythiopheneacetylene polymers, polybenzo[a]benzene polymers, polyphenanthrene polymers, and polynaphthalene polymers. These can be used alone or in combination of two or more. Polyurethane resins are preferred as the adhesive resin. By using polyurethane resins, an antistatic layer that combines flexibility and excellent adhesion can be formed.

[0090] The antifouling layer preferably contains a fluorinated compound. Among them, fluorinated polymers containing a perfluoropolyether backbone are preferred due to their excellent water repellency and ability to provide high antifouling properties. From the perspective of improving antifouling performance, perfluoropolyethers with a main chain structure that can be rigidly arranged side by side are particularly preferred. As the structural unit of the main chain backbone of the perfluoropolyether, perfluoroalkyl fusible compounds with branches having 1 to 4 carbon atoms are preferred, such as perfluoromethane oxide, (-CF2O-), perfluoroethylene oxide (-CF2CF2O-), perfluoropropylene oxide (-CF2CF2CF2O-), perfluoroisopropyl oxide (-CF(CF3)CF2O-), etc.

[0091] The printed layer can be a surface layer with a defined design or a full-coverage color layer. The printed layer can be formed by applying any suitable ink or paint. The ink or paint typically includes a binder, colorant, solvent, and any suitable additives that may be used as needed. Examples of binders include: chlorinated polyolefins (e.g., chlorinated polyethylene, chlorinated polypropylene), polyester resins, urethane resins, acrylic resins, vinyl acetate resins, vinyl chloride-vinyl acetate copolymers, and cellulose resins. The binder resin can be used alone or in combination of two or more. As for colorants, any suitable colorant can be used depending on the purpose. Specific examples of colorants include: inorganic pigments such as titanium dioxide, zinc dioxide, carbon black, iron black, iron oxide red, molybdenum chrome red, ultramarine, cobalt blue, chrome yellow, and titanium yellow; organic pigments or dyes such as phthalocyanine blue, indanthrin blue, isoindolinone yellow, benzidine yellow, quinacridone red, polyazo red, perylene red, and aniline black; metallic pigments formed from flake-like foils of aluminum, brass, etc.; and pearlescent pigments (pearl pigments) formed from flake-like foils coated with titanium dioxide mica, alkaline lead carbonate, etc.

[0092] The thickness of the functional layers can be appropriately set according to the purpose and application. The thickness of each functional layer is, for example, 0.1 μm to 2 μm, preferably 0.1 μm to 1.5 μm.

[0093] A-4. First Adhesive Layer

[0094] The first adhesive layer 20 preferably has a glass adhesion strength of 3.0 N / 25 mm to 20 N / 25 mm, more preferably 4.0 N / 25 mm to 15 N / 25 mm, and even more preferably 5.0 N / 25 mm to 12 N / 25 mm. If the glass adhesion strength is within the above range, sufficient adhesion can be achieved between the polarizing plate and the supporting substrate. It should be noted that the above-mentioned glass adhesion strength can be measured using a sample with the first adhesive layer formed on a 50 μm thick PET substrate as the test sample.

[0095] The first adhesive layer is formed by applying the adhesive composition to various substrates and subjecting them to drying, radiation irradiation, etc., as needed. When the first adhesive layer is formed on a release liner, it can be transferred from the release liner to the desired component (specifically, a support substrate or polarizing plate). Alternatively, the first adhesive layer can be formed directly on the support substrate or polarizing plate.

[0096] The thickness of the first adhesive layer is, for example, 2 μm to 50 μm, preferably 5 μm to 35 μm, and more preferably 10 μm to 25 μm.

[0097] As the adhesive composition forming the first adhesive layer, any suitable adhesive composition can be used. Examples include adhesive compositions made of rubber, acrylics, silicones, carbamates, vinyl alkyl ethers, polyvinyl alcohol, polyvinylpyrrolidone, polyacrylamide, cellulose, etc. Among these, acrylic adhesive compositions are preferred from the perspective of excellent optical transparency, as well as excellent adhesive properties, weather resistance, and heat resistance.

[0098] The above-mentioned acrylic adhesive composition, as a base polymer, comprises: a portion of a polymer containing a monomer component of (meth)acrylate and / or a (meth)acrylate polymer obtained from that monomer component. Specifically, the content of the (meth)acrylate polymer in the acrylic adhesive composition, converted from solids, is preferably 50% to 100% by weight, more preferably 60% to 100% by weight, further preferably 70% to 100% by weight, particularly preferably 80% to 100% by weight, and most preferably 90% to 100% by weight.

[0099] The weight-average molecular weight of the (meth)acrylic acid polymer is preferably 100,000 to 3,000,000, more preferably 150,000 to 2,000,000, even more preferably 200,000 to 1,500,000, and particularly preferably 250,000 to 1,000,000.

[0100] Examples of alkyl methacrylates include those having a straight-chain or branched alkyl group with 1 to 24 carbon atoms at the ester terminus. Alkyl methacrylates can be used alone or in combination of two or more.

[0101] Examples of the aforementioned alkyl methacrylates include linear or branched alkyl methacrylates having 4 to 9 carbon atoms. These alkyl methacrylates are preferred for their ability to readily achieve a balanced adhesive property. Specifically, examples include: n-butyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, isohexyl methacrylate, isohexyl methacrylate, 2-ethylhexyl methacrylate, isooctyl methacrylate, and isononyl methacrylate, which can be used alone or in combination of two or more.

[0102] Regarding the amount of the alkyl (meth)acrylate having an alkyl group having 1 to 24 carbon atoms at the ester terminus, relative to the total amount of the monofunctional monomer components forming the (meth)acrylate polymer, it is preferably 40% to 100% by weight, more preferably 50% to 100% by weight, and even more preferably 60% to 100% by weight.

[0103] Among the monomer components described above, the monofunctional monomer component may contain comonomers other than the aforementioned alkyl (meth)acrylate. The comonomers may be used as the remaining portion of the aforementioned alkyl (meth)acrylate in the monomer component (for example, 20% by weight or less, or, for example, 15% by weight or less, relative to the total amount of the monofunctional monomer component).

[0104] As for the aforementioned comonomers and their amounts, the comonomers and their amounts described in paragraphs 0029 to 0042 of Japanese Patent Application Publication No. 2016-157077 or in paragraphs 0022 to 0036 of Japanese Patent Application Publication No. 2016-190996 can be used. For example, examples of comonomers include: hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and other hydroxyl-containing (meth)acrylates; carboxyl-containing monomers such as (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and their anhydrides (e.g., maleic anhydride, itaconic anhydride, and other anhydride-containing monomers); and (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-methyl... amide-containing monomers such as oxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide; amino-containing monomers such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; epoxy-containing monomers such as glycidyl (meth)acrylate and methylglycidyl (meth)acrylate; cyano-containing monomers such as acrylonitrile and methacrylonitrile; N-vinyl-2-pyrrolidone and (meth)propylene. Monomers containing heterocyclic vinyl groups, such as acylmorpholine, N-vinylpiperidone, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazol, vinylpyridine, vinylpyrimidine, and vinyloxazole; monomers containing sulfonic acid groups, such as sodium vinylsulfonate; monomers containing phosphate groups, such as 2-hydroxyethylacryloyl phosphate; monomers containing imide groups, such as cyclohexylmaleimide and isopropylmaleimide; monomers containing isocyanate groups, such as 2-methacryloyloxyethyl isocyanate; and monomers containing cyclopentyl methacrylate and methyl methacrylate. Cyclohexyl acrylate, isobornyl acrylate, and other (meth)acrylates with alicyclic hydrocarbon groups; phenyl acrylate, phenoxyethyl acrylate, benzyl methacrylate, and other (meth)acrylates with aromatic hydrocarbon groups; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyltoluene; olefins and dienes such as ethylene, butadiene, isoprene, and isobutylene; vinyl ethers such as vinyl alkyl ethers; vinyl chloride; etc. The comonomer can be one or more types.

[0105] In addition to monofunctional monomers, polyfunctional monomers may also be included in the monomer components that form the above-mentioned (meth)acrylic acid polymers in order to adjust the cohesive force of the adhesive.

[0106] Polyfunctional monomers are monomers containing at least two unsaturated double bonds of functional groups such as (meth)acryloyl or vinyl groups. Examples include: ester compounds of polyols and (meth)acrylic acid such as polyethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, etc.; allyl methacrylate, ethylene methacrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, di(meth)acrylate, and di(meth)hexyl acrylate, etc. Among these, trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, and dipentaerythritol hexa(meth)acrylate may be used appropriately. One multifunctional monomer may be used alone or in combination of two or more.

[0107] The amount of multifunctional monomer used varies depending on its molecular weight, number of functional groups, etc. It is preferable to use 3 parts by weight or less, more preferably 2 parts by weight or less, and even more preferably 1 part by weight or less, relative to 100 parts by weight of the total amount of monofunctional monomers. Furthermore, as a lower limit, there is no particular limitation, but it is preferable to use 0 parts by weight or more, more preferably 0.001 parts by weight or more. By using the amount of multifunctional monomer within the above range, the adhesive strength can be improved.

[0108] The aforementioned (meth)acrylic acid polymers can be manufactured by any suitable method. For example, solution polymerization, radiation polymerization such as ultraviolet (UV) polymerization, bulk polymerization, emulsion polymerization, and other free radical polymerization methods can be appropriately selected. Various known substances, such as azo compounds and peroxides, can be used as free radical polymerization initiators. The reaction temperature is typically around 50–80°C, and the reaction time is 1–8 hours. Furthermore, solution polymerization is preferred among the above manufacturing methods. Ethyl acetate, toluene, etc., are generally used as solvents for the (meth)acrylic acid polymers. The solution concentration is typically around 20–80% by weight. Moreover, the obtained (meth)acrylic acid polymer can be any of the following: random copolymer, block copolymer, graft copolymer, etc.

[0109] The adhesive composition described above may contain a crosslinking agent. Examples of crosslinking agents include: isocyanate crosslinking agents, epoxy crosslinking agents, organosilicon crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, silane crosslinking agents, alkyl etherified melamine crosslinking agents, metal chelate crosslinking agents, and peroxides. The crosslinking agent may be a single agent or a combination of two or more. Among these, isocyanate crosslinking agents are preferred.

[0110] Examples of isocyanate crosslinking agents include: aromatic isocyanates such as toluene diisocyanate and xylene diisocyanate, alicyclic isocyanates such as isophorone diisocyanate, and aliphatic isocyanates such as hexamethylene diisocyanate.

[0111] More specifically, examples include: lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic diisocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, phenyl diisocyanate, and polymethylene polyphenyl isocyanate; trimethylolpropane / toluene diisocyanate trimer adduct (trade name: CORONATE L, manufactured by Nippon Polyurethane Industry Co., Ltd.); trimethylolpropane / hexamethylene diisocyanate trimer adduct (trade name: CORONATE HL, manufactured by Nippon Polyurethane Industry Co., Ltd.); and isocyanurate form of hexamethylene diisocyanate (trade name: CORONATE). Isocyanate adducts such as HX (manufactured by Nippon Polyurethanes Co., Ltd.), trimethylolpropane adduct of phenylene diisocyanate (trade name: D110N, manufactured by Mitsui Chemicals Co., Ltd.), trimethylolpropane adduct of hexamethylene diisocyanate (trade name: D160N, manufactured by Mitsui Chemicals Co., Ltd.); polyether polyisocyanates, polyester polyisocyanates, and their adducts with various polyols, as well as polyisocyanates that have been multifunctionalized with isocyanurate bonds, biuret bonds, urethane bonds, etc. Among these, aliphatic isocyanates are preferred due to their fast reaction rate.

[0112] Examples of peroxide-based crosslinking agents include: di(2-ethylhexyl) peroxide dicarbonate, di(4-tert-butylcyclohexyl) peroxide dicarbonate, di(sec-butyl) peroxide dicarbonate, tert-butyl peroxyneodecanate, tert-hexyl peroxynepentanoate, tert-butyl peroxynepentanoate, dilauroyl peroxide, dioctanoyl peroxide, 1,1,3,3-tetramethylbutyl peroxide isobutyrate, 1,1,3,3-tetramethylbutyl peroxide 2-ethylhexanoate, di(4-methylbenzoyl) peroxide, dibenzoyl peroxide, and tert-butyl peroxide isobutyrate. Among these, di(4-tert-butylcyclohexyl) peroxide, dilauroyl peroxide, and dibenzoyl peroxide, which exhibit excellent crosslinking reaction efficiency, are particularly preferred.

[0113] Regarding the mixing ratio of (meth)acrylic polymers and crosslinking agents, the crosslinking agent (solid component) is preferably about 0.001 to 20 parts by weight relative to 100 parts by weight of (meth)acrylic polymer (solid component), more preferably about 0.01 to 15 parts by weight, and even more preferably about 0.1 to 10 parts by weight.

[0114] The above-mentioned adhesive composition may further contain, as needed: ultraviolet absorbers; tackifiers such as rosin derivative resins, polyterpene resins, petroleum resins, and oil-soluble phenolic resins; plasticizers; fillers such as hollow glass microspheres; pigments; colorants; antioxidants; anti-aging agents; silane coupling agents, and various other additives. The amount of additives can be appropriately set according to the purpose. For example, regarding the amount of silane coupling agent, it is preferably 1 part by weight or less, more preferably 0.01 part by weight to 1 part by weight, and even more preferably 0.02 part by weight to 0.6 part by weight, relative to 100 parts by weight of the monofunctional monomer component forming the above-mentioned (meth)acrylic acid polymer.

[0115] The adhesive composition described above is preferably adjusted to a viscosity suitable for coating operations. Viscosity adjustment can be achieved by adding tackifying polymers, multifunctional monomers, etc., to partially polymerize the monomer components in the adhesive composition. This partial polymerization can be carried out before or after the addition of the tackifying polymers, multifunctional monomers, etc. The viscosity of the adhesive composition varies depending on the composition of the monomer components, the type of additives, and the mixing amount, so the preferred polymerization rate for partial polymerization is difficult to determine in a single statement. For example, the polymerization rate can be below 20%, preferably 3% to 20%, and more preferably around 5% to 15%. If the polymerization rate in partial polymerization exceeds 20%, the viscosity becomes excessively high, making coating on the substrate difficult.

[0116] A-5. Second adhesive layer

[0117] The second adhesive layer 40 typically has a glass adhesion strength of 1.0 N / 25 mm or more, preferably 2.0 N / 25 mm or more, and more preferably 2.5 N / 25 mm or more. The glass adhesion strength of the second adhesive layer 40 can be, for example, 10 N / 25 mm or less, 9.0 N / 25 mm or less, or 6.0 N / 25 mm or less. If the glass adhesion strength is within the above range, workability during reprocessing or peeling removal can be improved, and when the polarizing film laminate is adhered to the substrate, lifting peeling can be suppressed and a good adhesion condition maintained. Furthermore, the absolute value of the difference between the glass adhesion strength of the first adhesive layer and the glass adhesion strength of the second adhesive layer can be, for example, 0 N / 25 mm to 4.5 N / 25 mm. It should be noted that the above-mentioned glass adhesion strength can be measured using a sample with the second adhesive layer formed on a 50 μm thick PET substrate as the test sample.

[0118] The adhesion force of the second adhesive layer to the glass is preferably less than or equal to the adhesion force of the first adhesive layer to the supporting substrate, and more preferably less than the adhesion force of the first adhesive layer to the supporting substrate. Similarly, the adhesion force of the second adhesive layer to the glass is preferably less than or equal to the adhesion force of the first adhesive layer to the polarizer and the adhesion force of the second adhesive layer to the supporting substrate, and more preferably less than both. When the adhesion forces of the first adhesive layer and the second adhesive layer satisfy the above-described relationship, the effects of the present invention can be more appropriately obtained. It should be noted that the above-described adhesion forces can be adjusted to the desired values ​​by appropriately selecting the adhesive composition forming the first adhesive layer and / or the second adhesive layer, by adjusting the thickness of the adhesive layer, and by performing easy-bonding treatments (such as surface treatments like corona treatment, formation of easy-bonding layers, etc.) on the supporting substrate or polarizer.

[0119] In one embodiment, when the second adhesive layer is adhered to the glass plate by water-based adhesive application, the adhesion strength of the second adhesive layer to the glass plate (peel angle 90°, peel speed 300 mm / min, 23°C) four days after application is, for example, 0.2 N / 25 mm or more, preferably 0.3 N / 25 mm or more, more preferably 0.5 N / 25 mm or more, and even more preferably 0.8 N / 25 mm or more, for example, 5.0 N / 25 mm or less, and preferably 4.5 N / 25 mm or less. It should be noted that the above-mentioned adhesion strength to glass can be measured using a sample with the second adhesive layer formed on a 50 μm thick PET substrate as the test sample. The water-based adhesive application will be described in detail in section C.

[0120] The second adhesive layer is formed by applying the adhesive composition to various substrates and subjecting them to drying, radiation, or other methods as needed. For example, the second adhesive layer can be formed on a release liner and bonded to a support substrate together with the release liner. Alternatively, the second adhesive layer can be formed on a release liner, transferred from the release liner to the support substrate, and another release liner can be temporarily bonded thereon. The second adhesive layer can also be formed directly on the support substrate.

[0121] The thickness of the second adhesive layer is, for example, 5 μm to 100 μm, preferably 7 μm to 60 μm, and more preferably 10 μm to 40 μm.

[0122] As the adhesive composition forming the second adhesive layer, any suitable adhesive composition can be used as long as it achieves the aforementioned adhesion to glass. Examples include: rubber-based, acrylic-based, silicone-based, urethane-based, vinyl alkyl ether-based, polyvinyl alcohol-based, polyvinylpyrrolidone-based, polyacrylamide-based, and cellulose-based adhesive compositions. Among these, acrylic adhesive compositions are preferred due to their excellent optical transparency, adhesion properties, weather resistance, heat resistance, and water shielding properties. The same description applies to the adhesive composition for forming the first adhesive layer as described in section A-4. It should be noted that by using a (meth)acrylic polymer with a low amount of carboxyl monomer (e.g., a (meth)acrylic polymer in which the amount of carboxyl monomer in 100 parts by weight of the monofunctional monomer component forming the (meth)acrylic polymer is 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 1 part by weight or less, and even more preferably 0.5 parts by weight or less (e.g., 0 parts by weight)), and by using an adhesive composition with a low amount of silane coupling agent (e.g., an adhesive composition in which the amount of silane coupling agent is 1 part by weight or less, preferably 0 to 0.5 parts by weight, and more preferably 0 to 0.3 parts by weight relative to 100 parts by weight of the monofunctional monomer component forming the (meth)acrylic polymer), it is possible to prevent the excessive increase in the adhesion force to the glass over time. As a result, a polarizing film laminate with excellent workability for reprocessing and peeling removal can be obtained while suppressing lift-off peeling.

[0123] In one embodiment, the water absorption rate of the second adhesive layer is preferably 2% or more, for example, 3% or more, and even more than 5%. The water absorption rate of the second adhesive layer is preferably 15% or less, for example, 12% or less, and even more than 10%. If the water absorption rate is too low, high adhesion may sometimes be exhibited immediately after the water-based adhesive application, making further processing difficult. If the water absorption rate is too high, residual adhesive is easily generated during reprocessing and peeling removal. An adhesive layer with the above-mentioned water absorption rate can be obtained, for example, by introducing hydroxyl groups into the base polymer (preferably a (meth)acrylic) polymer, or by suppressing the gelation rate.

[0124] The water absorption rate mentioned above can be determined, for example, by the following method. In this case, multiple samples (e.g., N≥3) can be measured, and their average value can be taken as the water absorption rate.

[0125] <Water Absorption Rate>

[0126] An adhesive layer (20 μm thick) applied to the substrate was cut into 25 mm × 100 mm pieces along with the substrate. The substrate side was then attached to an aluminum plate (2 mm thick) using double-sided adhesive tape. This was used as the evaluation sample. Additionally, only the substrate (50 μm thick PET film) was attached to the aluminum plate using double-sided adhesive tape; this was used as the blank sample. Both the evaluation sample and the blank sample were immersed in construction water (e.g., water, or a diluted solution of film application concentrate (trade name "FILM-ON") (approximately 0.5% by weight)) at room temperature (e.g., 23°C) and removed after 96 hours. The water absorption rate can be calculated using the following formula based on the mass change of the evaluation sample and the blank sample before and after immersion.

[0127] Water absorption rate (mass%) = [(mass increase of the evaluation sample before and after impregnation - mass increase of the blank sample before and after impregnation) / mass of the evaluation sample before impregnation] × 100

[0128] A-6. Peeling the liner

[0129] Examples of release liner 50 include: paper, plastic film, polytetrafluoroethylene (PTFE) film, resin film with silicone treatment or fluorinated silicone treatment, etc.

[0130] A-7. Protective Substrate

[0131] As the protective substrate 60, any suitable substrate capable of protecting the exposed surface of the polarizing film laminate can be used, depending on the purpose. Specific examples include resin substrates such as polyvinyl chloride film and (meth)acrylic resin films such as PMMA.

[0132] The thickness of the protective substrate can be, for example, 0.1μm to 2mm, preferably 0.1μm to 1.5mm.

[0133] B. Separator

[0134] According to another aspect of the present invention, a partition wall is provided, which is a transparent partition wall that separates the space of an image display device having linearly polarized light emitted from the display screen, wherein the polarizing film laminate described in item A above is bonded by means of the second adhesive layer, such that the absorption axis of the polarizing element is substantially parallel to the vibration direction of the linearly polarized light emitted by the image display device.

[0135] Figure 3 This is a schematic diagram illustrating an example of a partition wall using the polarizing film laminate described in section A above. A space (room) 300 is separated by a pair of opposing walls 200, 220, another pair of opposing walls 210, 230 in a direction intersecting the walls 200, 220, a ceiling 240, and a floor 250. An image display device 400 is installed inside the space. The wall 200 is a full-length window made of transparent components (e.g., a total light transmittance of 70% or more), and the polarizing film laminate 100 is attached to it in such a way that it covers the portion corresponding to the image display device 400 when an observer views the space 300 from outside the wall 200. Furthermore, the polarizing film laminate 100 is arranged such that the vibration direction of the linearly polarized light emitted from the image display device 400 (arrow A direction) is substantially parallel to the absorption axis of the polarizer in the polarizing film laminate 100 (arrow B direction), specifically at an angle of 0°±10°, preferably 0°±5°, and more preferably 0°±3°.

[0136] According to the above scheme, since the linearly polarized light emitted by the image display device 400 is absorbed by the polarizing film laminate 100, it is possible to prevent the display content of the image display device 400 from being observed from the outside of the wall 200.

[0137] Alternatively, unlike the example shown, a portion of wall 200 may be a transparent partition (window). Furthermore, the transparent partition to which the polarizing film laminate is adhered is not limited to a window (including a full-length window); it can also be a door or partition, etc. The polarizing film laminate can be adhered to the entire transparent partition or only partially (where necessary).

[0138] C. Method for bonding polarizing film laminates

[0139] The polarizing film laminate described in item A is adhered to the substrate by making the surface of the second adhesive layer adhere closely to the substrate. In one embodiment, the adhesion of the polarizing film laminate described in item A to the substrate can be performed by applying water to the surface of the second adhesive layer of the polarizing film laminate and / or the surface of the substrate, and pressing the polarizing film laminate onto the substrate while squeezing the water sandwiched between the second adhesive layer and the substrate from their interface. (In this specification, the practice of having water between the second adhesive layer of the polarizing film laminate and the substrate and squeezing out the water for pressing is sometimes referred to as "water bonding".)

[0140] Immediately after water-based adhesive application, a small amount of water remains between the second adhesive layer and the substrate. Therefore, the adhesion of the polarizing film laminate to the substrate is at a level suitable for further processing. As the water dries and is removed over time, the adhesion increases, effectively suppressing subsequent peeling. It should be noted that during water-based application, pressing the polarizing film laminate against the back side with a scraper or similar tool can effectively remove residual water and air bubbles from the interface. Furthermore, the water sandwiched between the polarizing film laminate and the substrate is preferably purified water such as pure water or ion-exchanged water. Additionally, additives such as surfactants can be included as long as the desired effects of this invention are achieved. Surfactants are substances used to increase the slippage of the polarizing film laminate at the interface with the substrate (e.g., a glass plate) in the presence of water, facilitating positional adjustment. Therefore, the adhesion of the polarizing film laminate to the substrate is not significantly affected by the presence or absence of additives. There are no particular limitations on the amount of water provided; for example, approximately 0.5 mL / 100 cm². 2 ~ Approximately 1.0 mL / 100 cm 2 .

[0141] The adhesion strength of the polarizing film laminate to the substrate after 3 days from the time of application (peel angle 90°, peel speed 300 mm / min, 23°C) is preferably 1.0 N / 25 mm to 6.0 N / 25 mm, more preferably 2.5 N / 25 mm to 4.5 N / 25 mm.

[0142] In one embodiment, the adhesion force (peel angle 90°, peel speed 300 mm / min, 23°C) of the polarizing film laminate to the glass plate four days after application via water-based adhesive bonding is, for example, 0.2 N / 25 mm or more, preferably 0.3 N / 25 mm or more, more preferably 0.5 N / 25 mm or more, even more preferably 0.8 N / 25 mm or more, for example, 5.0 N / 25 mm or less, and preferably 4.5 N / 25 mm or less. If the adhesion force of the polarizing film laminate to the glass plate four days after application is within the above range, it can be easily peeled off for at least one week after application, exhibiting excellent reprocessability.

[0143] In one embodiment, the adhesion force (peel angle 90°, peel speed 300 mm / min, 23°C) of the polarizing film laminate to the glass plate 30 minutes after it is applied to the glass plate by water-based adhesive application is, for example, 0.01 N / 25 mm or more, preferably 0.02 N / 25 mm or more, for example, 2 N / 25 mm or less, and preferably 1 N / 25 mm or less.

[0144] Example

[0145] The present invention will now be specifically described through examples, but the present invention is not limited to these examples. Furthermore, unless otherwise specified, "parts" and "%" in the examples are based on weight.

[0146] (1) Thickness

[0147] Measurements were performed using a digital instrument (manufactured by Ozaki Manufacturing Co., Ltd., product name "PEACOCK").

[0148] (2) Glass adhesion

[0149] The adhesive force of the glass was measured using an adhesive / film peeling analysis device (manufactured by Kyowa Interface Science Co., Ltd., product name "VPA-H200") under the following conditions according to JIS Z0237 with N=3, and the average value was calculated.

[0150] Adhesive: Matsunami Glass Industry Co., Ltd., MICRO SLIDE GLASS S200423 water-ground edge t1.3 (size: 65×165mm, thickness: 1.2~1.5mm)

[0151] Test piece: A polarizing film laminate obtained in the examples or comparative examples, cut into 25×150mm pieces.

[0152] Adhesion method (dry): Without wetting the film, apply the adhesive layer of the polarizing film laminate to the object to be bonded, and then use a 2kg roller to move back and forth on it once.

[0153] Adhesion method (water-based): Spray film application liquid (approximately 0.5% by weight solution of film application concentrate (trade name "FILM-ON") diluted with water to an aqueous solution of approximately 200 times) onto the surface of the substrate and the adhesive layer of the polarizing film laminate. Apply the adhesive layer of the polarizing film laminate to the substrate. Press a scraper on it in the same manner as treating the back of the polarizing film laminate to expel air and application liquid from the interface between the two, thus adhering the polarizing film laminate to the substrate.

[0154] Measurement: After pasting, allow to stand for 30 minutes or 4 days (96 hours), then measure (pasting, standing, and measurement are carried out at 23°C and 50% RH).

[0155] Peeling angle: 90 degrees

[0156] Peeling speed: 300 mm / min

[0157] (3) Individual transmittance and polarization of polarizing element

[0158] The single-cell transmittance Ts, parallel transmittance Tp, and orthogonal transmittance Tc, measured using a UV-Vis-NIR spectrophotometer (V-7100, manufactured by Nippon Spectrophotometer Co., Ltd.), are used as the Ts, Tp, and Tc values ​​of the polarizer. These Ts, Tp, and Tc values ​​are Y values ​​measured using a 2-degree field of view (C light source) according to JIS Z8701 and corrected for visual sensitivity. The polarization degree is calculated using the following formula based on the obtained Tp and Tc.

[0159] Polarization (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0160] [Manufacturing Example 1: Preparation of Acrylic Adhesive Layer A]

[0161] (Preparation of acrylic polymer solutions)

[0162] A monomer mixture containing 81.8 parts butyl acrylate, 16 parts phenoxyethyl acrylate, 1.5 parts N-vinyl-2-pyrrolidone, 0.3 parts acrylic acid, and 0.4 parts 4-hydroxybutyl acrylate was added to a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet pipe, and condenser. Then, relative to 100 parts of the aforementioned monomer mixture (solid component), 0.1 parts of 2,2'-azobisisobutyronitrile (2,2'-azobisisobutyronitrile) as a polymerization initiator and 100 parts of ethyl acetate were added. While slowly stirring, nitrogen was introduced for nitrogen purging. The liquid temperature in the flask was maintained at approximately 55°C for 8 hours to prepare a solution of acrylic polymer A with a weight-average molecular weight (Mw) of 1.57 million and Mw / Mn = 3.3.

[0163] (Preparation of acrylic adhesive compositions)

[0164] Acrylic adhesive composition A is prepared by mixing 0.1 parts of isocyanate crosslinking agent (TAKENATE D160N, trimethylolpropane hexamethylene diisocyanate, manufactured by Mitsui Chemicals Co., Ltd.), 0.3 parts of peroxide crosslinking agent (benzoyl peroxide (trade name: NYPER BMT, manufactured by Nippon Yushi Co., Ltd.)) and 0.2 parts of silane coupling agent (trade name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) with 100 parts of the solid component of the acrylic polymer A solution.

[0165] The acrylic adhesive composition A obtained above was coated on one side of a polyethylene terephthalate film (release liner: manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., MRF38) treated with an organosilicon release agent, such that the thickness of the adhesive layer after drying is 15 μm. The film was then dried at 155°C for 1 minute to form an acrylic adhesive layer A on the surface of the release liner.

[0166] [Manufacturing Example 2: Preparation of Acrylic Adhesive Layer B]

[0167] (Preparation of acrylic polymer solutions)

[0168] A monomer mixture containing 94.9 parts by mass of butyl acrylate, 5 parts by mass of acrylic acid, and 0.1 parts by mass of 2-hydroxyethyl acrylate was added to a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet tube, and condenser. 0.1 parts by mass of 2,2'-azobisisobutyronitrile (2,2'-Azobisisobutyronitrile), used as a polymerization initiator, was added along with ethyl acetate, relative to 100 parts by mass of the solids in the monomer mixture. Nitrogen gas was introduced to purge the mixture while stirring slowly. The polymerization reaction was then carried out at approximately 55°C for 7 hours. Ethyl acetate was added to the resulting reaction solution to prepare a solution of acrylic polymer B with a polymer concentration adjusted to 30% by mass and a weight-average molecular weight of 2 million.

[0169] (Preparation of acrylic adhesive compositions)

[0170] Acrylic adhesive composition B is prepared by mixing 0.6 parts by mass of an isocyanate crosslinking agent (trade name: CORONATE L, trimethylolpropane toluene diisocyanate, manufactured by Nippon Polyurethane Kogyo Co., Ltd.), 0.2 parts by mass of a peroxide crosslinking agent (trade name: NYPER BMT, manufactured by Nippon Yushi Co., Ltd.) and 0.2 parts by mass of a silane coupling agent (trade name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) with 100 parts by mass of the polymer component of the acrylic polymer B solution.

[0171] The acrylic adhesive composition B obtained above was uniformly coated onto the surface of the release liner (a polyethylene terephthalate film treated with a silicone release agent) using a spray coating machine. Then, it was dried in an air-circulating constant temperature oven at 155°C for 70 seconds to form an adhesive layer B with a thickness of 20 μm on the surface of the release liner.

[0172] [Manufacturing Example 3: Preparation of Acrylic Adhesive Layer C]

[0173] (Preparation of acrylic polymer solutions)

[0174] In a reaction vessel equipped with a condenser, a nitrogen inlet tube, a thermometer, and a stirrer, 99 parts of butyl acrylate, 1.0 part of 4-hydroxybutyl acrylate, and 0.3 parts of 2,2'-azobisisobutyronitrile were added together with ethyl acetate. After reacting for 4 hours under a nitrogen atmosphere at 60°C, ethyl acetate was added to the reaction solution to obtain a solution containing an acrylic polymer with a weight average molecular weight of 1.65 million (solid content concentration 30%). Relative to 100 parts of the solid content of the aforementioned acrylic polymer solution, 0.3 parts of benzoyl peroxide (manufactured by Nippon Yushu Co., Ltd.: NYPER BMT), 0.1 parts of trimethylolpropane xylene diisocyanate (Takenafil D110N, Mitsui Takeda Chemical Co., Ltd.), and 0.2 parts of an acetyl silane coupling agent (manufactured by Soken Chemical Co., Ltd.: A-100) were mixed to prepare acrylic adhesive composition C.

[0175] The acrylic adhesive composition C obtained above was uniformly coated onto the surface of a release liner (a polyethylene terephthalate film treated with a silicone release agent) using a spray coating machine. Then, it was dried in an air-circulating constant temperature oven at 155°C for 70 seconds to form an adhesive layer C with a thickness of 20 μm on the surface of the release liner.

[0176] [Example 1]

[0177] (Making of polarizing plates)

[0178] As a thermoplastic resin substrate, a single side of the resin substrate was corona treated with a strip-shaped, amorphous polyethylene terephthalate (PET) copolymer film with a Tg of approximately 75°C.

[0179] A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA resin obtained by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a ratio of 9:1 and dissolving it in water.

[0180] A PVA-based resin layer with a thickness of 13 μm was formed by coating the corona-treated surface of a resin substrate with the above-mentioned PVA aqueous solution and drying it at 60°C, thus creating a laminate.

[0181] The resulting laminate was unidirectionally stretched to 2.4 times its original length in an oven at 130°C (air-assisted stretching treatment).

[0182] Next, the laminate was immersed in an insoluble bath (an aqueous solution of boric acid prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40°C for 30 seconds (insoluble treatment).

[0183] Next, the polarizer is immersed in a dyeing bath (an iodine aqueous solution prepared by mixing iodine and potassium iodide in a weight ratio of 1:7 relative to 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds (dyeing treatment) while adjusting the concentration to achieve the desired monomer transmittance (Ts) of the final polarizer.

[0184] Next, it is immersed in a crosslinking bath at a liquid temperature of 40°C (an aqueous solution of boric acid prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid relative to 100 parts by weight of water) for 30 seconds (crosslinking treatment).

[0185] Then, the laminate is immersed in a boric acid aqueous solution (boric acid concentration 4% by weight, potassium iodide concentration 5% by weight) at a liquid temperature of 70°C, while being unidirectionally stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different circumferential speeds at a total stretch ratio of 5.5 times.

[0186] Then, the laminate was immersed in a cleaning bath at a liquid temperature of 20°C (an aqueous solution of 4 parts by weight of potassium iodide mixed with 100 parts by weight of water) (cleaning treatment).

[0187] Then, while drying in an oven maintained at approximately 90°C, it comes into contact with heated rollers made of SUS, whose surface temperature is maintained at approximately 75°C (drying shrinkage treatment).

[0188] Thus, a polarizing element with a thickness of about 5 μm is formed on the resin substrate, resulting in a laminate with a resin substrate / polarizing element structure.

[0189] A cellulose triacetate (TAC) film with a hard coating (3 μm hard coating thickness, 25 μm TAC thickness) was bonded as a protective layer onto the surface of the obtained polarizer (the side opposite to the resin substrate) using a UV-curable adhesive. Next, the resin substrate was peeled off to obtain a polarizing plate with a structure of [polarizer / TAC protective layer]. The resulting polarizer has a monomer transmittance of 43% and a polarization degree of 99.9%.

[0190] (Fabrication of polarizing thin film laminate)

[0191] Adhesive layer A is transferred from the release liner to the polarizer side surface of the polarizing plate obtained above. A support substrate (50 μm thick PET film: manufactured by Toray Industries, Inc., product name "Lumirror S10", water absorption rate <1%) is then bonded to the adhesive layer of the obtained polarizing plate with adhesive layer. Next, adhesive layer C is transferred to the support substrate surface. Thus, a polarizing film laminate with the structure of [TAC protective layer / polarizer / adhesive layer A / PET support substrate / adhesive layer C] is obtained.

[0192] [Example 2]

[0193] Adhesive layer A is transferred from the peel-off pad to the polarizer side surface of the polarizing plate obtained in the same manner as in Example 1. A PET resin film with an acrylic adhesive layer (manufactured by Lintec Corporation, product name "1501E", total thickness: 70 μm (of which PET thickness is 50 μm)) is bonded to the adhesive layer of the resulting polarizing plate with the adhesive layer, with the resin film facing the adhesive layer A. Thus, a polarizing film laminate with the structure of [TAC protective layer / polarizer / adhesive layer A / PET resin film / acrylic adhesive layer] is obtained.

[0194] [Example 3]

[0195] Adhesive layer A is used instead of adhesive layer C, and otherwise the same procedure is followed as in Example 1 to obtain a polarizing film laminate with the structure of [TAC protective layer / polarizing element / adhesive layer A / PET support substrate / adhesive layer A].

[0196] [Example 4]

[0197] Adhesive layer A is transferred from the peel-off pad to the polarizer-side surface of the polarizing plate obtained in the same manner as in Example 1. A polyethylene film with an acrylic adhesive layer (manufactured by Nitto Denko Corporation, product name "E-MASK R300", total thickness: 70 μm) is bonded to the adhesive layer of the resulting polarizing plate with the adhesive layer, with the polyethylene film facing the adhesive layer A. Thus, a polarizing film laminate with the structure of [TAC protective layer / polarizer / adhesive layer A / polyethylene film / acrylic adhesive layer] is obtained.

[0198] [Example 5]

[0199] Adhesive layer A is transferred from the peel-off pad to the polarizer-side surface of the polarizer obtained in the same manner as in Example 1. A PET resin film (manufactured by Nitoms, Inc., product name "M6330", total thickness: 75 μm (of which PET thickness is 50 μm)) with an acrylic adhesive layer is bonded to the adhesive layer of the resulting polarizer with the adhesive layer, with the resin film facing the adhesive layer A. Thus, a polarizer film laminate with the structure of [TAC protective layer / polarizer / adhesive layer A / PET resin film / acrylic adhesive layer] is obtained.

[0200] [Example 6]

[0201] Adhesive layer A is transferred from the peel-off pad to the polarizer-side surface of the polarizer obtained in the same manner as in Example 1. A PET resin film with an acrylic adhesive layer (manufactured by Riken Technos Corp., product name "SS50TO", total thickness: 75 μm (of which PET thickness is 50 μm)) is bonded to the adhesive layer of the resulting polarizer with the adhesive layer, with the resin film facing the adhesive layer A. Thus, a polarizer film laminate with the structure of [TAC protective layer / polarizer / adhesive layer A / PET resin film / acrylic adhesive layer] is obtained.

[0202] [Comparative Example 1]

[0203] Adhesive layer A is transferred from the peel-off pad to the polarizer-side surface of the polarizer obtained in the same manner as in Example 1. A PET film with an acrylic adhesive layer (manufactured by 3M, product name "SH2CLAR", adhesive layer thickness: 26 μm, PET film thickness: 50 μm) is bonded to the adhesive layer of the resulting polarizer with the adhesive layer, with the PET film facing the adhesive layer A. This yields a polarizer film laminate with the structure of [TAC protective layer / polarizer / adhesive layer A / PET support substrate / acrylic adhesive layer].

[0204] [Comparative Example 2]

[0205] Adhesive layer B is used instead of adhesive layer C, and otherwise the same procedure is followed as in Example 1 to obtain a polarizing film laminate with the structure of [TAC protective layer / polarizing element / adhesive layer A / PET support substrate / adhesive layer B].

[0206] [Comparative Example 3]

[0207] Adhesive layer A is transferred from the peel-off pad to the polarizer-side surface of the polarizer obtained in the same manner as in Example 1. A PET film containing an olefin elastomer and an adhesive layer (manufactured by PANAC Corporation, product name "Gelpolyclear50UV-IJII", adhesive layer thickness: 35 μm, PET film thickness: 50 μm) is bonded to the adhesive layer of the resulting polarizer with the adhesive layer A in a manner where the PET film is opposite to adhesive layer A. Thus, a polarizer film laminate with the structure of [TAC protective layer / polarizer / adhesive layer A / PET film / olefin elastomer adhesive layer] is obtained.

[0208] "Stripping Evaluation"

[0209] The polarizing film laminates (1000mm × 500mm) obtained in Examples 1-6 and Comparative Examples 1-3 were adhered to the glass partition using an adhesive layer disposed on the surface opposite to the protective layer. Adhesion was performed using a water-based adhesive application.

[0210] Specifically, a film application liquid (an aqueous solution (approximately 0.5% by weight) obtained by diluting a concentrated film application liquid (trade name "FILM-ON") 200 times with water) is sprayed onto the surface of the adhesive layer of the glass partition and the polarizing film laminate. The adhesive layer of the polarizing film laminate is then adhered to the designated position on the glass partition, which is wetted with the application liquid, and its position is adjusted while sliding it. Next, a scraper is pressed against the back side (protective layer side surface) of the polarizing film laminate, and slid along the back side of the polarizing film laminate, gradually pressing the polarizing film laminate onto the glass partition. This forces air and the application liquid out from the interface between the two, thus adhering the polarizing film laminate to the glass partition.

[0211] Two hours and one month after the operation (drainage) of extruding air and water (construction fluid), the peelability of the polarizing film laminate when lifted by finger was evaluated based on the following criteria in order to peel it off from the glass septum. The evaluation results after 2 hours and 1 month are shown in Table 1 as workability (initial reprocessability) and peelability over time, respectively.

[0212] ○: Can be easily peeled off.

[0213] △: Peeling is laborious and difficult.

[0214] ×: Cannot be peeled off.

[0215] Evaluation of Floating Stripping

[0216] For each polarizing film laminate obtained in Examples 1-6 and Comparative Examples 1-3, samples of A4 size and 500mm × 1000mm size were prepared. Similar to the peelability evaluation, each sample was adhered to a glass partition using a water-based adhesive. After 500 hours at 60°C and 90% RH, the A4 size samples (N=3) were adhered to the glass partitions of the conference room (approximately 30 partitions in total, N=3-4 for each sample), and the adhesion was checked after 6 months of installation, evaluated based on the following criteria. Furthermore, for polarizing film laminates other than those in Example 4, samples of 846mm × 846mm size (N=3) were prepared and adhered to an 850mm × 850mm glass partition using a water-based adhesive, similar to the above method. The adhesion was then checked after 150 hours (1 week) at 60°C and 90% RH, evaluated based on the following criteria. The results are shown in Table 1.

[0217] ○: No buoyancy peeling occurred in any of the samples.

[0218] △: Lifting and peeling occurred in some samples.

[0219] ×: Lifting and peeling occurred in all samples.

[0220] [Table 1]

[0221]

[0222] [Example 7]

[0223] An acrylic resin film (40 μm thick: manufactured by Toyo Kobutsu Co., Ltd., product name "HX40UC") was used as the support substrate. Otherwise, the process was the same as in Example 1 to obtain a polarizing film laminate with the structure of [TAC protective layer / polarizing element / adhesive layer A / acrylic support substrate / adhesive layer C].

[0224] [Example 8]

[0225] A TAC film (40 μm thick: manufactured by Konica Minolta, product name "KC4UY") was used as the support substrate, and otherwise the same procedure as in Example 1 was performed to obtain a polarizing film laminate with the structure of [TAC protective layer / polarizing element / adhesive layer A / TAC support substrate / adhesive layer C].

[0226] Curved Evaluation

[0227] Evaluation samples were prepared by transferring adhesive layer A to the polarizer side surface of the polarizer obtained in the same way as in Example 1, resulting in a polarizer with a structure of [TAC protective layer / polarizer / adhesive layer A]; polarizer 2 with an adhesive layer and a structure of [TAC protective layer / polarizer (thickness 29 μm) / TAC protective layer / acrylic adhesive layer] (manufactured by Nitto Denko Corporation, product name "TEG1465DU"); and polarizer film laminates of Examples 7-8 and Comparative Example 3, cut into 10 cm × 10 cm pieces. The evaluation samples were placed on a smooth glass plate with the adhesive layer side surface facing up, and the initial curl value was measured. Next, approximately 1.0 mL of film application liquid (an aqueous solution obtained by diluting film application concentrate (trade name "FILM-ON") 200 times with water) was sprayed to uniformly wet the entire adhesive layer surface, and the curl value was measured immediately after spraying and after 15 minutes. It should be noted that the maximum value of the upper surface position (height) of the evaluation sample with the glass surface as the reference is taken as the curl value. The curl value when the adhesive layer is convex is recorded as a positive (+) value, and the curl value when a concave surface is formed is recorded as a negative (-) value. The measurements were performed with N=3, and the average value of the obtained curl values ​​is shown in Table 2.

[0228] [Table 2]

[0229]

[0230] As shown in Table 2, polarizing plates 1 and 2, which lack a supporting substrate and a second adhesive layer, exhibit significant curling when the adhesive layer surface comes into contact with water. This curling occurs during water-based application, reducing workability. In contrast, the polarizing film laminate with a structure in which a supporting substrate and a second adhesive layer are provided on the polarizing plate with the adhesive layer suppresses curling when the adhesive layer surface comes into contact with water, thus exhibiting adaptability for water-based application. Furthermore, this effect is more readily achieved when the water absorption rate of the supporting substrate is low.

[0231] Industrial availability

[0232] The polarizing film laminate of the present invention can be suitably used as an indoor personal privacy protection film, etc.

Claims

1. A polarizing thin film laminate, comprising a polarizing plate including a polarizing element, a first adhesive layer, a supporting substrate, and a second adhesive layer sequentially stacked. The adhesion force of the second adhesive layer to glass is greater than 2.0 N / 25 mm and less than 10 N / 25 mm at a peel angle of 90° and a peel speed of 300 mm / min. Water is applied to the surface of the second adhesive layer and / or the surface of the glass plate to be bonded. While pressing the glass plate with water, the water sandwiched between the second adhesive layer and the glass plate is squeezed out from their interface. Four days after pressing, the adhesion force to the glass is 0.2 N / 25 mm to 5.0 N / 25 mm at a peel angle of 90° and a peel speed of 300 mm / min. The polarizing film laminate is attached to a transparent partition wall that separates the space of an image display device that emits linearly polarized light from the display screen, using the second adhesive layer, in such a way that the angle between the absorption axis of the polarizing element and the vibration direction of the linearly polarized light emitted from the image display device is in the range of 0°±10°.

2. The polarizing thin film laminate according to claim 1, wherein, The water absorption rate of the supporting substrate is less than 5.0%.

3. The polarizing thin film laminate according to claim 1, wherein, The polarizing plate also includes a protective layer disposed on at least one side of the polarizing element.

4. The polarizing thin film laminate according to claim 1, wherein, The supporting substrate includes a substrate body and a functional layer disposed on at least one side of the substrate body.

5. The polarizing thin film laminate according to claim 4, wherein, The functional layer is selected from at least one of the antistatic layer and the antifouling layer.

6. The polarizing thin film laminate according to claim 1, wherein, The thickness from the polarizing plate to the second adhesive layer is 50 μm to 500 μm.

7. The polarizing thin film laminate according to claim 1, wherein, A release liner is laminated on the side of the second adhesive layer opposite to the side on which the support substrate is configured.

8. A partition wall, which is a transparent partition wall separating a space inside an image display device that emits linearly polarized light from its display screen, wherein, The polarizing film laminate according to any one of claims 1 to 6 is bonded by means of the second adhesive layer, such that the angle between the absorption axis of the polarizing element and the vibration direction of the linearly polarized light emitted by the image display device is in the range of 0° ± 10°.

9. The partition wall according to claim 8, wherein it is a window, wall, door or partition.

Citation Information

Patent Citations

  • Protective film for polarizer and its manufacturing method

    JP2001343529A

  • Manufacturing method of thin polarizing film

    JP2012073580A

  • Polarizing film with adhesive layer, and image display device

    JP2016157077A

  • Adhesive composition, adhesive layer for transparent conductive layer, adhesive layer-attached polarizing film, and image display device

    JP2016190996A

  • Transparent film

    WO2001037007A1